Effizientes Projektmanagement in Einer-für-Alle-Nachnutzungsprojekten - Katharina Kalchner; Florian Allwein; Nicolai Krüger (IU Internationale Hochschule, 2025)
The digitalization of public services is a critical driver of Germany's competitiveness and future readiness. The "Einer-für-Alle" (EfA) approach, where software is developed by one federal state and implemented by others, exemplifies efforts to streamline public sector digital transformation. However, progress has been hindered by inefficiencies in project management and a lack of tailored methodologies. This study adopts a mixed-method approach, combining quantitative and qualitative research, to develop a comprehensive guideline for project managers engaged in EfA initiatives. By addressing the unique characteristics of the public sector, our framework integrates hybrid project management techniques and contextualized process models. The study not only advances applied research in hybrid project management but also provides practical tools to enhance the efficiency and success of future public service digitalization projects.
Keywords: H; Z; 004; Projektmanagement; EfA-Nachnutzungsprojekte; Digitalisierung der öffentlichen Verwaltung; Methodischer Projekt-Leitfaden